Penerapan Model Pembelajaran Inkuiri untuk Meningkatan Aktifitas Belajar Siswa pada Mata Pelajaran Ilmu Pengetahuan Alam Kelas IX.A SMP Negeri 1 Gangga - Siti Nurkhasanah (Universitas Pendidikan Mandalika (UNDIKMA), 2019)
This study aimed to improve students’ learning activities in Science subjects with material inheritance through Inquiry learning models. The research method used was classroom action research conducted in three cycles. The subjects of this study were students of class IX.A Gangga SMP N 1. The data collection technique used was the observation sheet. Data of the research were analyzed by using descriptive qualitative and quantitative analysis. The results of the study showed that there was a significant increase from cycle I to cycle II, and from cycle II to cycle III to the components studied. From the results of which, therefore, it could be concluded that the implementation of Inquiry learning models had an effect on students learning activities. This was proved by the higher value of students learning activities in each cycle of the actions.